Optimization of the catalytic activity of a ZnCo2O4 catalyst in peroxymonosulfate activation for bisphenol A removal using response surface methodology. (December 2018) - Hu, Limin; Zhang, Guangshan; Liu, Meng; Wang, Qiao; Wang, Peng
Abstract: An effective peroxymonosulfate activator, ZnCo2 O4, was synthesized through a microwave-assisted method. According to response surface methodology (RSM) using Box-Behnken design (BBD), the effects of four parameters, microwave temperature, microwave time, calcination time and calcination temperature, were investigated, and the results show that both the microwave temperature and calcination temperature have a great influence on the catalytic activity during the preparation process. In addition, a quadratic model is valid for computing and predicting the observed responses. The characteristics of the synthesized ZnCo2 O4 catalyst were analyzed with various equipments. The results show that the ZnCo2 O4 nanosheets are cubic crystals with a spinel structure and a high surface area of 105.90 m 2 ‧g −1 . Under the conditions of [ZnCo2 O4 ] = 0.2 g‧L −1 and [PMS]/[BPA]molar = 2.0, the bisphenol A degradation efficiency reaches 99.28% within 5 min in the ZnCo2 O4 /PMS system. ZnCo2 O4 possesses great stability and reusability according to recycling experiments. In addition, the possible active radical species were confirmed through quenching experiments and EPR detection, indicating that surface-bound SO4 - and OH play vital roles during the degradation process. Graphical abstract: Schematic representation of BPA degradation with ZnCo2 O4 synthesized using microwave-assisted method in ZnCo2 O4 /PMS system, where the optimal ZnCo2 O4 can be identified through response surface methodology. According EPR detection, SO4 - and OH were generated through the ZnCo2 O4 /PMS system and they are considered as the main active radicals. Highlights: ZnCo2 O4 is successfully synthesized using microwave-assisted method. Response surface methodology is used to analyze the optimal preparation condition. ZnCo2 O4 shows excellent degradation performance in the presence of PMS. ZnCo2 O4 is a talented PMS activator for its high catalytic activity and stability.